PENGARUH FINANCIAL DISTRESS, AKTIVITAS OPERASIONAL DAN PROFITABILITAS TERHADAP RETURN SAHAM PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2018 - Rizqi, Miftaqul; Sutjahyani, Dewi (JEA17: Jurnal Ekonomi Akuntansi, 2019)
ABSTRACTOne of the mainstay sectors in the Indonesian capital market is the mining sector. Mining companies require large capital to carry out their operations, so many mining companies enter the capital market to obtain investment and strengthen their financial position. The objectives to be achieved from the formulation of the problems that have been described are to determine the partial and simultaneous influence of Financial Distress, Operational Activities and Profitability on Stock Returns on mining companies listed on the Indonesia Stock Exchange in 2011-2018. The population is 41 companies. Samples obtained by purpose sample technique were 4 companies. The independent variables used are Altman Z Score, Operating Cash Flow, Investment Cash Flow, Funding Cash Flow, Net Profit Margin, Return On Equity and Return On Asset, while the dependent variable used is stock returns. In this study, the analytical method used is multiple linear regression analysis method, with the classic assumption test including normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. Hypothesis testing uses the t statistical test and the f statistical test, and the coefficient of determination test. The results of this study indicate that Financial Distress as measured by altman z- score, Operational Activities as measured by AKO, AKI and AKP, Profitability as measured by NPM, ROE and ROA partially or simultaneously does not significantly influence stock returns. The coefficient of determination produces a value of 19.6% which means that stock returns are influenced by Financial Distress, Operational Activities and Profitability by 19.6% while the remaining 80.4% is influenced by other factors not included in the study. Keywords: Financial Distress, Operational Activities, Profitability, Stock Return